Emerging highly pathogenic avian influenza (H5N8) virus in migratory birds in Central China, 2020 - Jiasong Xiong; Hao Zhou; Lifang Fan; Gongliang Zhu; Yong Li; Guang Chen; Jun Zhang; Jundong Li; Hesong Zheng; Wei Feng; Jing Chen; Guoxiang Yang; et al. (Emerging Microbes and Infections)
Eleven highly pathogenic avian influenza H5N8 viruses (clade 2.3.4.4b) were detected in migratory birds in Central China between November and December 2020, which were highly homologous to strains isolated in Europe from October to December 2020. Phylogenetic analysis indicated that the strains in the study possibly spread from Siberia by migratory birds. In this study, we found H5N8 virus infection in migratory birds could cause severe pathological damage and high viral load in multiple organs.